Econometric Analysis of Discrete Reforms - Kireyev, Alexei (IMF Working Papers; Working Paper, 2001)
The paper suggests an econometric methodology for testing the effectiveness of reforms implemented in one major step, id est, discrete reforms. The methodology is based on the exogeneity properties of variables in an econometric model. The paper specifies the preconditions for setting up an appropriate model; suggests an economic interpretation of the tests for weak, strong, and superexogeneity; and illustrates this methodology by applying it to two cases of instantaneous reforms. The exogeneity properties of variables in a correctly specified econometric model may help uncover information on the preparation, implementation, and the outcome of such reforms, which could be useful for future policy advice.